Challenges and barriers to the European Union expansion to the Balkan Region - Costa, Bruno Ferreira <<[HerausgeberIn]>> (Information Science Reference, an imprint of IGI Global, 2022)
"This book studies the political challenges of the enlargement and possible constraints within the European Union in the Balkan region, providing frameworks and research findings that tackle the many issues they are facing"--
Bibliographie: Seite 314-361
Premier Reference Source